Kesenjangan Ekspektasi-Kinerja Dalam Keterampilan Umum Akuntansi - Sakina Nusarifa Tantri; Nabella Duta Nusa; Raise Pranadya (Jurnal Akuntansi dan Governance, 2020)
Preparations for the ASEAN Economic Community (AEC) 2025 require accountants to play an important role in an era of openness that demands information accountability. The lack of generic accounting skills from an industry point of view motivates researchers to conduct quantitative research aimed at investigating whether there are gaps in expectation-performance in generic accounting skills. The data of this study were collected through survey using questionnaires as the instrument. The research sample is accounting vocational educators and users of accounting graduates in Indonesia. This study identified the gap between the expectations of accounting graduates users related to the importance of general accounting skills for career success with generic accounting skills performed by accounting graduates. This research is expected to contribute as a material consideration for educators in accounting vocational higher education institutions in Indonesia in preparing learning models in order to accommodate the needs of the work field of accounting.